Pemanfaatan limbah padat ampas tebu sebagai bahan bakar pembangkit listrik - Huzaiva, Regyana Julya; Anastasya, Stefi; Mua, Moh Rizki; Cahyani, Renita (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The potential for sugar cane in 2021 is 447,339 hectares. This area increased by around 56,661 hectares to 504,000 hectares. The total production of sugar cane is 2,350,809 tons in 2021 and will increase by 2,740,000 tons in 2023. The increase in production is in line with the amount of solid waste bagasse produced. Solid waste in the form of bagasse amounting to 756,582.72 tons in 2021 is a processing opportunity and requires downstream processing. Sugarcane bagasse has a calorific value of 4282.35 cal/gr. The compound content in sugarcane bagasse solid waste is (22.4%), C/N ratio (89.6%), N (0.25%), phosphate content (0.15-0.22%), and K2O (0.2-0.38%). Dry bagasse can be one of the main materials that supplies heating value to boilers and turbines for power plants. Utilization of sugarcane bagasse has the potential to produce a calorific value of 1.380 billion kcal which can be allocated to electricity generation needs.